PENGARUH BUDAYA ORGANISASI DAN DISIPLIN PEGAWAI TERHADAP KINERJA PEGAWAI DI KEPOLISIAN DAERAH LAMPUNG - Agus Purnomo; Eko Sujarwo (e-JKPP, 2016)
In improving the performance of employees of organizations or institutions through several ways through increasing employee discipline and enhancing a good organizational culture. The purpose of this study was to determine and analyze the influence of organizational culture and work discipline on employee performance in the Lampung Regional Police.This study used a quantitative descriptive analysis design, with organizational culture and work discipline as independent variables and employee performance as the dependent variable. The sample used in the study amounted to 100 respondents with proportional random method (proportional random sampling). The analysis used was validity test, reliability test and multiple linear regression analysis.Based on the research results, it can be seen that: (1) The results of hypothesis testing partially show that organizational culture partially has a significant effect on employee performance in the Lampung Regional Police. (2) The results of the hypothesis test partially show that work discipline partially has a significant effect on employee performance in the Lampung Regional Police. (3) The simultaneous hypothesis test results show that the variables of organizational culture and work discipline simultaneously have a significant effect on employee performance in the Lampung Regional Police. While the results of the Determination Coefficient (R Square) are known to have a value of 0.671, meaning that organizational culture and work discipline have an influence of 67.1% on the performance of employees in the Lampung Regional Police.